Bureaucracy and Political Parties: Political Clientelism in Contestation of Power in Tanjung Jabung Timur Regency - Muhammad, Hatta Abdi; Yusuf, Muhammad (Jurnal Politik Indonesia: Indonesian Political Science Review, 2020)
Political relation with bureaucracy is an essential concern because the contestation of power in the regions has conflicted with democratization and the principle of bureaucratic neutrality. Recent studies point out the politicization of bureaucracy in placing positions and government decision-making processes, but the discussion about political party patron-client with bureaucracy is very limited. This paper discusses explicitly the clientelism of political parties with the civil servants in the election of public officials in the Tanjung Jabung Timur regency. This study applies a descriptive qualitative methodology to analyze the depth of phenomena that has been happening by using secondary and primary data from various informants. Various data are coded, analyzed interactively, and confirmed its validity, then presented systematically. The results show that the leaders in the regions only experience a shift in the party while the actor's character still owned the legacy of the New Order regime. The central locus of patronage is still concentrated in political parties; National Mandate Party has a clientelism networking through the dominance of a bureaucratic structure with a promotion-degradation system. The civil servants change the resources to maintain a position or even to get a higher one. This paper's implication showed that civil servants' performance is relatively based on loyalty to the ruling party rather than using a merit system. This paper underlines the main challenge of democracy in the region and bureaucratic reform, and it is the massive informal political practices that are considered reasonable.